Network Abroad and Culture: Global Individual-Level Evidence - Riccardo Turati (Institute of Labor Economics (IZA), 2024)
This paper analyzes whether natives with a network abroad have a distinctive cultural stance compared to similar individuals without such connections within the same region. Using individual-level data on connectedness from the Gallup World Poll across 2,256 within-country regions over 148 countries, it characterizes the cultural stance based on three traits: pro-social behavior, religiosity and gender-egalitarian attitudes. The paper shows that natives who have a connection abroad are characterized by stronger pro-social behavior, religiosity and genderegalitarian attitudes. To address potential biases arising from omitted variables, it controls for an extensive array of individual characteristics and region-by-year fixed effects. The results are also consistent after employing comprehensive measures of connectedness, employing matching techniques, and assessing selection biases related to unobservable factors. Finally, by leveraging both country and individual-level heterogeneity, the analysis indicates that the pro-social behavior stance of connected individuals is fairly consistent across different contexts and individuals, while the findings on religiosity and gender-egalitarian attitudes are more sensitive to local and individual factors. The paper therefore shows that factors enhancing or dampening this relation are cultural trait specific.
Keywords: F22; O15; Z10; 330; cultural traits; connectedness; social remittances; international migration